2017
DOI: 10.1002/jlb.5mr0717-306r
|View full text |Cite
|
Sign up to set email alerts
|

Immunotherapy for cardiovascular disease

Abstract: Heart failure (HF), the final stage of pathological cardiac hypertrophy, is a major cause of hospitalization and mortality. The role of inflammation in the pathogenesis of HF has been extensively studied, with great emphasis on proinflammatory cytokines. Yet, clinical trials targeting these cytokines failed to become a credible therapeutic strategy for HF. More recent studies are increasingly highlighting an active role for T cells in the progression of HF pathology. As a result, a number of novel immunotherap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 62 publications
(157 reference statements)
0
3
0
Order By: Relevance
“…Inflammation plays a crucial role in the development of cardiovascular disease (CVD). Chronic inflammation within the arterial wall, especially in the context of atherosclerosis, plays a significant role in driving the progression of the disease [ 7 ]. The inflammatory response entails the activation of immune cells and the secretion of pro-inflammatory cytokines and chemokines, resulting in the recruitment and accumulation of immune cells at the site of injury [ 8 ].…”
Section: Reviewmentioning
confidence: 99%
“…Inflammation plays a crucial role in the development of cardiovascular disease (CVD). Chronic inflammation within the arterial wall, especially in the context of atherosclerosis, plays a significant role in driving the progression of the disease [ 7 ]. The inflammatory response entails the activation of immune cells and the secretion of pro-inflammatory cytokines and chemokines, resulting in the recruitment and accumulation of immune cells at the site of injury [ 8 ].…”
Section: Reviewmentioning
confidence: 99%
“…Although medications used to treat pulmonary fibrosis, such as pirfenidone, show an ability to decrease cardiac fibrosis, they result in minimal improvement in diastolic function [95]. As a subset of lymphocytes, regulatory T cells (Tregs) have demonstrated remarkable anti-inflammatory and cardioprotective properties [5,[96][97]. Many studies have shown its role as an immune regulator of unwanted immune responses as well as a regulator of pro-inflammatory T cells [98].…”
Section: Immune Cell Therapymentioning
confidence: 99%
“…Surprisingly, the emphasis of many current therapies applied to treat atherosclerosis and thrombosis has been put on coping with the onset of acute inflammatory states. It is noteworthy that statins can not only reduce the cholesterol level, but also play an anti-inflammatory role ( 3 ). This study, therefore, aims to more specifically reduce inflammatory activities during atherosclerosis using colchicine and interleukin (IL)-1β antibodies or other modes targeting IL-6 or IL-1 receptors ( 4 ).…”
Section: Introductionmentioning
confidence: 99%